Improving the Pharmacodynamics and In Vivo Activity of ENPP1‐Fc Through Protein and Glycosylation Engineering. Issue 1 (20th October 2020) - Stabach, Paul R.; Zimmerman, Kristin; Adame, Aaron; Kavanagh, Dillon; Saeui, Christopher T.; Agatemor, Christian; Gray, Shawn; Cao, Wenxiang; De La Cruz, Enrique M.; Yarema, Kevin J.; Braddock, Demetrios T.
Abstract : Enzyme replacement with ectonucleotide pyrophosphatase phospodiesterase‐1 (ENPP1) eliminates mortality in a murine model of the lethal calcification disorder generalized arterial calcification of infancy. We used protein engineering, glycan optimization, and a novel biomanufacturing platform to enhance potency by using a three‐prong strategy. First, we added new N‐glycans to ENPP1; second, we optimized pH‐dependent cellular recycling by protein engineering of the Fc neonatal receptor; finally, we used a two‐step process to improve sialylation by first producing ENPP1‐Fc in cells stably transfected with human α‐2, 6‐sialyltransferase (ST6) and further enhanced terminal sialylation by supplementing production with 1, 3, 4‐ O ‐Bu3 ManNAc. These steps sequentially increased the half‐life of the parent compound in rodents from 37 hours to ~ 67 hours with an added N‐glycan, to ~ 96 hours with optimized pH‐dependent Fc recycling, to ~ 204 hours when the therapeutic was produced in ST6‐overexpressing cells with 1, 3, 4‐ O ‐Bu3 ManNAc supplementation. The alterations were demonstrated to increase drug potency by maintaining efficacious levels of plasma phosphoanhydride pyrophosphate in ENPP1‐deficient mice when the optimized biologic was administered at a 10‐fold lower mass dose less frequently than the parent compound—once every 10 days vs. 3 times a week. We believe these improvements represent a general strategy to rationally optimize protein therapeutics.